On the karyology and morphology of Chironomus jonmartini Lindeberg (Diptera, Chironomidae) - Hirvenoja, Mauri; Michailova, Paraskeva (Entomologica Fennica, 1997)
A detailed description of the karyotype of Chironomus jonmartini Lindeberg as well as data for its polymorphism are presented. The polymorphism is realized by heterozygous inversions and a high percentage of additional "B", chromosomes. Males, females, pupae and larvae are also redescribed. C. jonmartini is compared morphologically with a karyologically unidentified species of the genus Chironomus, the males of which are to a certain extent similar to it.